2019
DOI: 10.1108/sajbs-05-2018-0059
|View full text |Cite
|
Sign up to set email alerts
|

Corporate distress, troubled debt restructurings and equity stripping

Abstract: Purpose The focus on excessive corporate leverage as a key factor influencing bank loan delinquency has come into sharp focus in recent times. However, not much analysis has been undertaken on the factors driving corporate distress in emerging economies. Focusing on India as a case study, the purpose of this paper is to investigate the impact of a particular category of corporate debt restructuring (CDR) proposed by the Indian central bank over the last decade in leading an attempt to address bank loan delinqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Debt restructuring, company must propose to the bank and the other creditors process of debt rescheduling, debt refinancing and debt discounting in order to prevent insolvency and or bankruptcy. Result from Ghosh (2019) when analyzing corporate debt restructurings in India as the emerging country, he found that firms which have successfully exit debt restructuring are more profitable, less levered, and spend longer time in restructuring process. Actually GIAA can follow the nearer sister company, PT Krakatau Steel Persero Tbk (KRAS) which is on processing the loan restructuring that was start in 2019, The CEO Mr. Silmy Karim said recently to the news (Kompas, 2020) “If able to accomplish, this is the biggest debt restructuring in the history of Indonesia.” But all of the restructuring process need patience and time to reveal, thus the government must set long-term time setting for this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Debt restructuring, company must propose to the bank and the other creditors process of debt rescheduling, debt refinancing and debt discounting in order to prevent insolvency and or bankruptcy. Result from Ghosh (2019) when analyzing corporate debt restructurings in India as the emerging country, he found that firms which have successfully exit debt restructuring are more profitable, less levered, and spend longer time in restructuring process. Actually GIAA can follow the nearer sister company, PT Krakatau Steel Persero Tbk (KRAS) which is on processing the loan restructuring that was start in 2019, The CEO Mr. Silmy Karim said recently to the news (Kompas, 2020) “If able to accomplish, this is the biggest debt restructuring in the history of Indonesia.” But all of the restructuring process need patience and time to reveal, thus the government must set long-term time setting for this.…”
Section: Discussionmentioning
confidence: 99%
“…, flight utilization, service excellence, customer experience, revenue diversification, support between government companies, and others internal or external supports, but we are not talking about organizational and operational things, we're talking about finance things which I've depicted into « DDCC » as the 4 financial solutions Figure1:(1) Debt restructuring, company must propose to the bank and the other creditors process of debt rescheduling, debt refinancing and debt discounting in order to prevent insolvency and or bankruptcy. Result fromGhosh (2019) when analyzing corporate debt restructurings in India as the emerging country, he found that firms which have successfully exit debt restructuring are more profitable, less levered, and spend longer time in restructuring process. Actually GIAA can follow the nearer sister company, PT Krakatau Steel Persero Tbk (KRAS) which is on processing the loan restructuring that was start in 2019, The CEO Mr. Silmy Karim said recently to the news (Kompas, 2020) "If able to accomplish, this is the biggest debt restructuring in the history of Indonesia."…”
mentioning
confidence: 99%
“…(B. N. state that debt restructuring is a way to avoid company liquidation through an agreement with creditors with certain conditions. Meanwhile, according to (Ghosh, 2019) is an adjustment or rearrangement of the debt structure that reflects an agreement with the debtor to plan for the fulfillment of its financial obligations. The purpose of debt restructuring is to provide support in the form of leeway for companies that are experiencing financial difficulties so that they can get out of these problems within a certain period (Cheng, 2015).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Restrukturisasi adalah perubahan model bisnis, kepemilikan, struktur aset atau struktur modal suatu perusahaan agar dapat terus mencapai tujuannya (Silva & Saito, 2018). Restrukturisasi juga sebagai cara untuk menghindari likuidasi atau tuntutan pailit oleh kreditur dengan menyepakati syarat tertentu yang dikenal dengan restrukturisasi utang (Ghosh, 2019;Greenwood et al, 2020). Berbagai bentuk skema restrukturisasi utang antara lain renegosiasi utang dan rescheduling utang (Tedeschi et al, 2021), debt to asset swap (Kang, 2020), dan debt to equity swap (Cepec & Grajzl, 2020).…”
Section: Pendahuluan Latar Belakangunclassified